The Procedure of Government Undertaking Liability in front of the Parliament (Journal of Legal Studies, 2018)
The Constitutional provisions regulate the Government possibility to undertake the political liability for a program, a general policy statement or a draft law in front of the Parliament. The purpose of Government political liability for its initiative consists in its decision to continue the given mandate of trust only under the term of the approval for the program, the general policy statement or draft law submitted in joint session of the Chamber of Deputies and Senate.